Application of Rice Straw Compost with Different Bioactivators on the Growth and Yield of Rice Plant - Barus, Yunita (UNIVERSITY OF LAMPUNG, 2012)
Turnover of organic matters to the soil can increase the efficiency of chemical fertilizers, improve the plant growth and sustain the environment. Field experiment was carried out in the Buyut Udik Village, Gunung Sugih District, Central Lampung from May to August 2009.Â Rice straw was composted by three kinds of decomposer (bioactivator A, B, and C). Rice straw compost (2 Mg ha-1) was applied to the paddy-field soil that was planted by rice (Oryza sativa) of Ciherang Variety. The experiment was arranged in a randomized block design with three replicates. The results showed that application of rice straw compost reduced the numbers of empty grain per tiller compared to control (without compost) in which control had the highest percentage of empty grain (15.9%). The application of rice straw compost that was decomposed by bioactivator A gave the highest numbers of grain per panicle and yield per plot as followed 162.5 seed and 33 kg plot-1, respectively.Â Application of various rice straw composts that were decomposed by three kinds of bioactivator increased the rice grain up to 13-26% compared to control.